Projecting the Intramural ASEAN Norms into Extramural Terrain - Constructivism: Does TAC Work in the South China Sea? - Ratih Indraswari (Parahyangan Centre for International Studies, Parahyangan Catholic University, 2014)
Abstract: This article examines the role of ASEAN's norms in managing dispute over the South China Sea. ASEAN shares the beliefs that the settlement of differences or disputes by peaceful means and the abandonment of the threat or use of force are necessary to ensure the stability over the region. It attempts to analyze the possibility of exporting this intramural norm of ASEAN's model of dispute settlement into an extramural terrain and seeks to answer the question whether ASEAN's norm of cooperation can alter claimants' perception towards each other, and thus in return will constrain the urge to solve the dispute by force.